1970
DOI: 10.1161/01.res.26.3.397
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Basis of the Sheet-Flow Concept of the Pulmonary Alveolar Microcirculation in the Cat

Abstract: The purpose of this study was to describe quantitatively the geometric organization of the pulmonary alveolar capillary bed. Conventional representation of these vessels as a tight network of circular cylindrical tubes (tube-flow model) was contrasted with a suggested alternative of a continuous sheet bounded on two sides by endothelium held apart by connective tissue and cellular posts (sheet-flow model). A vascular space-tissue ratio, VSTR, is defined as the ratio of vascular lumen volume to the circumscribi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(29 citation statements)
references
References 13 publications
2
27
0
Order By: Relevance
“…The fourth observed pattern in this study was capillary recruitment occurring suddenly as capillary transmural pressure exceeded alveolar pressure, consistent with the idea of sheet flow described by Fung, Sobin, and colleagues (5,19). Godbey et al (9) showed that, as capillary transmural pressure exceeded alveolar pressure, the capillary networks tended to recruit as a sheet when alveoli were relatively undistended.…”
supporting
confidence: 88%
“…The fourth observed pattern in this study was capillary recruitment occurring suddenly as capillary transmural pressure exceeded alveolar pressure, consistent with the idea of sheet flow described by Fung, Sobin, and colleagues (5,19). Godbey et al (9) showed that, as capillary transmural pressure exceeded alveolar pressure, the capillary networks tended to recruit as a sheet when alveoli were relatively undistended.…”
supporting
confidence: 88%
“…The lung's unique hemodynamic properties are attributable to the so-called sheet structure of alveolar capillaries (8). According to this view, blood flow occurs not through tubular capillaries, as in systemic beds, but through two apposed sheet-like endothelial layers.…”
Section: Regulation Of the Properties Of The Alveolar-capillary Barrimentioning
confidence: 99%
“…In its essence, this theory suggested (and the morphological studies supported) that the pulmonary microvasculature consisted of two thin sheets of endothelium through which the blood flowed. The only interruptions in this continuous sheet were posts of endothelial tissue that connected the membranes together (Sobin et al, 1970). This configuration would then give the vasculature a distensibility that was only limited by the large number of posts holding the two layers together and the prevailing alveolar pressures on either side of the membrane (Sobin et al, 1972).…”
Section: Effect Of Vascular Compliance On Pulmonary Blood Flowmentioning
confidence: 99%